Studi Program Youth Entrepreneurship And Employment Support Services Pada Peternakan Kambing Di Kecamatan Gondang Kabupaten Tulungagung - Dyah Deci Dwi Lestari; Novita Dewi Kristanti; Siti Azizah (Lembaga Pengembangan Kinerja Dosen, 2024)
Tulungagung Regency was chosen to implement the YESS program because the majority of its people rely on the agricultural sector as their main livelihood and raising livestock as a side business. Geographically, the location of the Tulungagung Regency area is also quite strategic with abundant natural resources, thus supporting it as a target for implementing the Program. This research was carried out for 1 month from March 10 2023 to April 15 2023. In this research primary data and secondary data were obtained. Primary data was obtained from interviews and observations of 7 breeders who received benefits from competitive grants from the YESS Program in 2022, goat breeders as key informants in Gondang District, Tulungagung Regency and Expert Informants who came from YESS Program implementers from the Tulungagung Agriculture Service and program facilitators. Secondary data was obtained from literature. From the research, the results showed that the YESS program was considered successful in improving livestock farmers' skills, facilitating market access, increasing access to financing and activating institutional policies and media for youth involvement in rural areas. The suggestion for this research is that it is necessary to carry out further analysis regarding the obstacles that occur in implementing the YESS program.